POWER QUALITY ANALYSIS AT BUILDING OF POLITEKNIK NEGERI AMBON - LORY MARCUS PARERA; MARCEAU. A.F HAURISSA; MARSELIN JAMLAY (CV KULTURA DIGITAL MEDIA, 2022)
Power quality determines the reliability of electrical energy transmission which reflects the parameters of voltage, frequency, frequency, balance, and waveform. Electrical quality in a building is required due to abnormal effects on current, voltage, and frequency. By measuring it can be seen whether or not the abnormal electrical quality in the Ambon State Polytechnic's electrical system. The method used is data collection through literature study and observation of research locations, as well as descriptive analysis with a statistical approach. The Ambon State Polytechnic receives electricity from a power plant with a three-phase wire system. The load is supplied by a 3-phase transformer 20 kV/380 V With a power capacity of 250 kVA. carried out using a Power Analyzer where the tool for one day (24 hours) records electrical data for Polnam testing. Through tabulation and data analysis, there are several facts that there are abnormal conditions both in voltage, current, and frequency because the magnitude is outside the set standard. The results of the recommendation of the need for interference estimation begin with the selection of the right method.